2003
DOI: 10.1002/jbm.a.10600
|View full text |Cite
|
Sign up to set email alerts
|

TEGDMA‐induced toxicity in human fibroblasts is associated with early and drastic glutathione depletion with subsequent production of oxygen reactive species

Abstract: Triethylene glycol dimethacrylate (TEGDMA) is a dentin-bonding agent and a major component of various dental restorative biomaterials. TEGDMA monomers are released from dental resins and induce dental pulp inflammation and necrosis. In this study, we have investigated the mechanism of TEGDMA-induced cytotoxicity of fibroblasts. Treatment of cultured human gingival and pulpal fibroblasts with 0.1-3 mM of TEGDMA for 24 h induced a concentration-dependent and variable cytotoxic effect. Fifty percent of toxicity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
139
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 27 publications
5
139
0
12
Order By: Relevance
“…S11B). A number of lines of evidence have shown that deficiencies in intracellular GSH impair cellular antioxidant defenses and result in the accumulation of ROS [33,34]. In our study, pretreatment with NAC and GSH reduced the curcumin-induced increase in mitochondrial superoxide levels, whereas pretreatment with BSO, ethacrynic acid, DEM, or BCNU potentiated it (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 50%
“…S11B). A number of lines of evidence have shown that deficiencies in intracellular GSH impair cellular antioxidant defenses and result in the accumulation of ROS [33,34]. In our study, pretreatment with NAC and GSH reduced the curcumin-induced increase in mitochondrial superoxide levels, whereas pretreatment with BSO, ethacrynic acid, DEM, or BCNU potentiated it (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 50%
“…HEMA induced apoptosis has been linked to the decrease in intracellular glutathione (GSH) levels and the production of reactive oxygen species (ROS) in the cells. [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, they posses certain advantages compared to other cell types used in the literature, e.g. HELA cells, fibroblasts [15]. HUVEC are human, normal, endothelial cells, which are directly involved in all the inflammatory, allergic reactions and tumor outgrowths.…”
Section: Discussionmentioning
confidence: 99%